2019
DOI: 10.1177/0886260519876035
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Taking Propensity and Sensation Seeking in Survivors of Adverse Childhood Experiences

Abstract: Risk-taking propensity and sensation seeking are developmentally meaningful traits for emerging adults, individuals ages 18 to 25 years. Adverse childhood experiences (ACEs) of childhood abuse and neglect, exposure to domestic violence, residing with a substance abusing or mentally ill caregiver, and growing up with an incarcerated family member negatively impact the well-being of emerging adults. However, the specific association between ACEs and risk-taking propensity and sensation seeking has not been previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 73 publications
2
6
0
Order By: Relevance
“…That greater levels of childhood emotional abuse are linked to the development of trait impulsivity and sensation seeking is largely supportive of previous research (Babad et al, 2019;Bornovalova et al, 2008;Braquehais et al, 2010;Shin et al, 2015). The present study replicated these results, showing that men who had experienced more childhood emotional abuse reported greater sexual sensation seeking, which was subsequently associated with state impulsivity, state anxiety, and coercive CUR.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…That greater levels of childhood emotional abuse are linked to the development of trait impulsivity and sensation seeking is largely supportive of previous research (Babad et al, 2019;Bornovalova et al, 2008;Braquehais et al, 2010;Shin et al, 2015). The present study replicated these results, showing that men who had experienced more childhood emotional abuse reported greater sexual sensation seeking, which was subsequently associated with state impulsivity, state anxiety, and coercive CUR.…”
Section: Discussionsupporting
confidence: 90%
“…Because this association is indirect, it is critical to understand potential mediators of the relationship between child abuse and coercive CUR. Prior research suggests that impulsivity and sensation seeking (i.e., the need for novel, complex sensations and experiences accompanied by a willingness to take physical or social risks to obtain such experiences) may mediate this relationship, as they are common trait-level sequelae of childhood emotional abuse (Babad et al, 2019; Bornovalova et al, 2008; Shin et al, 2015). Victims of childhood emotional abuse may engage in sensation seeking as the result of maladaptive coping mechanisms.…”
Section: Distal Trait-level Risk Factors Of Coercive Curmentioning
confidence: 99%
“…However, this cumulative effect is not observed in all cases. For example, cumulative ACEs are not associated with increased risk for intimate partner violence (Nikulina et al, 2021) or with increased risk-taking and sensation seeking traits (Babad et al, 2019). This suggests that the relationship between cumulative ACEs and adverse outcomes is nuanced.…”
Section: Individual and Cumulative Acesmentioning
confidence: 99%
“…Finally, we used a cross‐sectional research design, limiting our ability to determine the direction of the relationships of interest. Although sensation seeking is presumed to be a biologically based personality trait, thus preceding alcohol use, it is possible that sensation seeking can also be an outcome of epigenetic factors such as psychological (Babad et al., 2019; Kerig, 2019) or physical (i.e., head injury; Liebel et al., 2021; O'Jile et al., 2004) trauma. Similarly, some researchers have suggested that similar epigenetic factors are associated with substance misuse (Jones et al., 2021) and that the relationship between epigenetic factors and addiction may be mediated by sensation seeking behavior (Hamilton & Nestler, 2019).…”
Section: Discussionmentioning
confidence: 99%